Motivační systém pro zefektivnění práce zaměstnanců ve vybraném podniku - Čížková, Petra (Vysoké učení technické v Brně. Fakulta podnikatelská, 2017)
Tato diplomová práce na téma: Motivační systém pro zefektivnění práce zaměstnanců ve vybraném podniku je rozdělena na dvě hlavní části – teoretickou a praktickou. Cílem práce je nejprve zanalyzovat stávající motivační systém ve výrobním podniku a následně navrhnou jeho zlepšení k docílení vyšší efektivity práce zaměstnanců. Teoretická část práce bude zaměřena na vysvětlení základních pojmů spjatých s touto problematikou. Praktická část se bude věnovat vybranému podniku a stávajícímu motivačnímu systému a v návaznosti na zjištěné údaje bude navrhnuta buď úpravu stávajícího motivačního systému anebo úplně nový motivační systém.

This diploma thesis deals with the topic of incentive system to streamline the work of employees in the manufacturing plant and it is divided into two main parts. The theoretical background part and the practical part. The goal of the thesis is to first analyze existing incentive system to streamline the work of employees in the manufacturing plant and then propose its improvements in line with the achieving higher efficiency of employees work. In the theoretical background chapter, author aims at explanation of basics concepts connected with this problematic. The practical part deals with the existing incentive system and after finding the results author will recommend maybe any modification of existing system or just completely new one.
Motivational System For More Effective Work of Employees in Selected Company
Keywords: Motivace; stimulace; hodnocení zaměstnanců; odměňování zaměstnanců; spokojenost zaměstnanců; formy motivace; řízení lidských zdrojů; Motivation; stimulation; Employee assessment; remuneration of employees; employee satisfaction; motivation forms of remuneration; leading of human resources